Factors affecting healthy lifestyle behaviors of nursing students - Dural, Gül; Aktürk, Ümmühan (Tuba UÇAR, 2021)
Aim:This descriptive study was conducted to determine nursing students' healthy lifestyle behaviors and the factors affecting them. Methods: The population of the research consisted of 1st, 2nd, 3rd and 4th grade students enrolled in a nursing program at a university in the fall semester of the 2021-2022 academic year. The research was completed with 500 students who agreed to participate. The research data were collected using the Personal Information Form and the Healthy Lifestyle Behaviors II Scale. Number, percentage, mean, t-test, and analysis of variance (ANOVA) tests were used to evaluate the data. Results: Students' Healthy Lifestyle Behaviors II Scale mean total score was 127.85±24.02 (min: 52, max: 208) and it was seen to be at a moderate level. It was determined that the variables including class, education type, income level, current residence, and health center visiting frequency affect the scale's total score. Conclusion: In the study, it was seen that the healthy lifestyle behaviors of nursing students were at a moderate level. It may be suggested to make arrangements to bring healthy lifestyle behaviors to nursing students' education.

Amaç: Bu araştırma, hemşirelik öğrencilerinin sağlıklı yaşam biçimi davranışlarının ve etkileyen faktörlerin belirlenmesi amacıyla tanımlayıcı tipte yapılmıştır. Yöntem: Araştırmanın evrenini 2021-2022 eğitim öğretim yılı güz yarıyılında bir üniversitede hemşirelik programına kayıtlı olan 1, 2, 3 ve 4. sınıf öğrencileri oluşturmuştur. Araştırma katılmayı kabul eden 500 öğrenci ile tamamlanmıştır. Araştırmada veriler Kişisel Bilgi Formu ve Sağlıklı Yaşam Biçimi Davranışları II Ölçeği kullanılarak toplanmıştır. Verilerin değerlendirmesinde sayı, yüzde, ortalama, t-testi ve varyans analizi (ANOVA) testleri kullanılmıştır. Bulgular: Öğrencilerin Sağlıklı Yaşam Biçimi Davranışları II Ölçeği toplam puan ortalaması 127.85±24.02 (min: 52, max: 208) olup orta düzeyde olduğu görülmüştür. Sınıf, öğrenim türü, gelir durumu, şu ana yaşanılan yer ve sağlık merkezine gitme sıklığı değişkenlerinin ölçek toplam puanı üzerinde etkili olduğu saptanmıştır. Sonuçlar: Çalışmada öğrencilerin sağlıklı yaşam biçimi ölçeği puan ortalamalarının orta düzeyde olduğu görülmüştür. Hemşirelik öğrencilerinin eğitimine sağlıklı yaşam biçimi davranışları kazandırılmasına yönelik düzenlemeler yapılması önerilebilir.
Hemşirelik öğrencilerinin sağlıklı yaşam biçimi davranışlarını etkileyen faktörler
Keywords: Preventative Health Care; Koruyucu Sağlık Hizmetleri